Load swing rejection for double-pendulum tower cranes using energy-shaping-based control with actuator output limitation. (June 2020) - Ouyang, Huimin; Tian, Zheng; Yu, Lili; Zhang, Guangming
Abstract: For the controller design of tower cranes, the swing of load is always regarded the crane as a single-pendulum model, however in practical applications, such as when the hook mass can not be ignored, the tower crane dynamic system presents a double-pendulum nature. In this case, the dynamic characteristics analysis and controller design for such cranes becomes more complicated. In addition, many researches do not take into account the real situation of the actuator, that is, in actual tower cranes, the output torque/force can not be infinite due to the actual design constraints of the actuator. When the output torque reaches the limit value in some cases, the control performance is greatly reduced. According to the above, after simplifying the tower crane dynamic model, this paper presents a nonlinear controller based on energy-shaping to solve the above problems. The stability of the closed-loop system is proved by the Lyapunov technique and LaSalle's invariance theorem. Under a large number of simulation results, the proposed controller has good control performance and robustness. Highlights: The load sway reduction problem in double-pendulum tower crane system is investigated. The nonlinear controller with limited output value is presented. The control performance is demonstrated by comparative simulations.